Sex differences in the outcome of juvenile social isolation on HPA axis function in rats. (21st April 2016) - Pisu, M.G.; Garau, A.; Boero, G.; Biggio, F.; Pibiri, V.; Dore, R.; Locci, V.; Paci, E.; Porcu, P.; Serra, M.
Highlights: Female rats are insensitive to the acute stress-induced increase in allopregnanolone levels. Social isolation decreased steroidogenesis in both male and female rats. Social isolation affects stress reactivity, emotionality and plasticity in a sex dimorphic way. Abstract: Women are more likely than men to suffer from anxiety disorders and major depression. These disorders share hyperresponsiveness to stress as an etiological factor. Thus, sex differences in brain arousal systems and their regulation by chronic stress may account for the increased vulnerability to these disorders in women. Social isolation is a model of early life stress that results in neurobiological alterations leading to increased anxiety-like and depressive-like behaviors. Here we investigated the sex difference in the effects of post-weaning social isolation on acute stress sensitivity and behavior in rats. In both sexes, social isolation at weaning reduced basal levels of the neuroactive steroid allopregnanolone in the brain and of corticosterone in plasma. Moreover, acute stress increased plasma corticosterone levels in both group-housed and socially isolated male and female rats; however this effect was greater in male than female rats subjected to social isolation. Intriguingly, group-housed female rats showed no change in plasma and brain levels of allopregnanolone after acute foot-shock stress. The absence of stress-induced effects on allopregnanolone synthesis might be due to the physiologically higher levels of this hormone in females vs. males. Accordingly, increasing allopregnanolone levels in male rats blunted the response to foot-shock stress in these animals. Socially isolated male, but not female, rats also display depressive-like behavior and increased hippocampal brain-derived neurotrophic factor (BDNF). The ovarian steroids could "buffer" the effect of this adverse experience in females on these parameters. Finally, the dexamethasone (DEX) suppression test indicated that the chronic stress associated with social isolation impairs feedback inhibition in both sexes in which an increase in the abundance of glucocorticoid receptors (GRs) in the hippocampus was found. Altogether, these results demonstrate that social isolation affects neuroendocrine reactivity to stress, plasticity and emotionality in a sexually dimorphic manner.